Image Steganography Using LSB Along With IDEA Algorithm (International Journal of Engineering and Computer Science, 2016)
Security is one of the most challenging aspects for information exchange in the World Wide Web. So this is an approach to find out the best solution for providing necessary protection to our data against malicious attacks from intruders.Cryptography and Steganography are the two major techniques that are being used worldwide for enhancing the security of data in secret communication. Steganography is the method through which existence of the original message is kept secret from a third party. In steganography the original message is hidden into the cover medium. Cryptography converts information from its original form (plaintext) easily understood by anyone into an unreadable form (cipher text) that does not express or mean anything. In this paper we are using steganography to hide the message applied together with cryptography so that we can enhance the security of the data. We are using LSB algorithm for steganography along with IDEA algorithm for cryptography.